Temperature-driven massless Kane fermions in HgCdTe crystals - F. Teppe (Nature Portfolio, 2016)
Kane fermions are predicted to be tunable with external parameters such as temperature. Here, Teppe et al. show a band structure evolution of bulk HgCdTe as temperature is tuned across topological phase transition, demonstrating that Kane fermions change sign in rest-mass and remain constant in velocity.